Elastic Properties of Chimpanzee Craniofacial Cortical Bone. Issue 12 (15th November 2016) - Gharpure, Poorva; Kontogiorgos, Elias D.; Opperman, Lynne A.; Ross, Callum F.; Strait, David S.; Smith, Amanda; Pryor, Leslie C.; Wang, Qian; Dechow, Paul C.
ABSTRACT: Relatively few assessments of cranial biomechanics formally take into account variation in the material properties of cranial cortical bone. Our aim was to characterize the elastic properties of chimpanzee craniofacial cortical bone and compare these to the elastic properties of dentate human craniofacial cortical bone. From seven cranial regions, 27 cylindrical samples were harvested from each of five chimpanzee crania. Assuming orthotropy, axes of maximum stiffness in the plane of the cortical plate were derived using modified equations of Hooke's law in a Mathcad program. Consistent orientations among individuals were observed in the zygomatic arch and alveolus. The density of cortical bone showed significant regional variation ( P  < 0.001). The elastic moduli demonstrated significant differences between sites, and a distinct pattern where E3  > E2  > E1 . Shear moduli were significantly different among regions ( P  < 0.001). The pattern by which chimpanzee cranial cortical bone varies in elastic properties resembled that seen in humans, perhaps suggesting that the elastic properties of craniofacial bone in fossil hominins can be estimated with at least some degree of confidence. Anat Rec, 299:1718–1733, 2016. © 2016 Wiley Periodicals, Inc.